The Correlation between Human Capital and Gross Added Value in the Bioeconomy Sectors at the European Union (EU) Country Level - Neagu, Olimpia; Dumiter, Florin; Braica, Alexandra; Jimon, Stefania Amalia; David, Gabriela (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2019)
The paper aims to prove the link between human capital and gross added value in bioeconomy sectors in the EU countries. Data from EUROSTAT data base regarding employment and gross added value in 6 bioeconomy sectors were used in a cross-country regression analysis. The econometric analysis of cross-country data shows a positive correlation between human capital in bioeconomy sectors and their gross output in 2015 in 26 European countries. It is found also that the correlation is stronger in the highly developed economies as in the central-eastern countries, as well as in the European economy.